Dynamics of morphological parameters of the thyroid gland in hypertensive SHR rats upon administration of propylthiouracil. - Pobelensky, K. O.; Kolot, N. V.; Protsenko, E. S.; Padalko, V. I.; Bozhok, G. A.; Legach, E. I.; Pobelensky О. N. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. The main clinical manifestations of thyroid gland (TG) diseases are associated with the influence of thyroid hormones on the cardiovascular system. At the same time, hypothyroidism as well as hyperthyroidism increase the risk of arterial hypertension. Based on this, the development of an experimental model that combines thyroid pathology and hypertension is relevant. From this point of view, the hypertensive SHR rats is a valuable object of study, since the course of arterial hypertension in these animals corresponds to the signs of human hypertension. Objective. Study of the dynamics of the morphological parameters of the thyroid gland in SHR rats with prolonged administration of propylthiouracil (PTU). Methods. Female SHR rats were used in the experiments; drinking water contained a 0.1% solution of PTU. TG was taken on the 17th, 25th, 31st, 39th and 47th days of the experiment, subjected to histological examination and staining with hematoxylin / eosin according to standard methods. We analyzed the average height of the follicular epithelium, the average follicle area, the nuclear cytoplasmic ratio (NCR) of thyrocytes, the ratio of the number of thyrocytes to fibroblasts per 50 μm2 (T/FB). Results. It was established that the height of the epithelium, NCR, and the area of the follicles change irregularly during the intake of PTU: at first, fluctuations of indicators are observed, and starting from 31st day they are stabilized. In general, after 47 days of receiving PTU, the average height of the follicular epithelium increased by 0.7 μm, the average area of the follicles – by 182 μm2, and NCR – by 0.11. In the stroma of the gland, activation of fibroblast proliferation was observed as evidenced by a decrease in the T/FB ratio from 2.87 to 0.54. Conclusion. When using a solution for drinking with 0.1% PTU for 47 days characteristic changes of hypertrophy and hyperplasia are observed in the thyroid tissue of hypertensive SHR rats. Stabilization of morphological parameters is observed after 30 days of taking PTU.